Assistance in Accelerating Halal Certification through the Self-Declare Scheme for Food/Beverage MSME Actors in Ponteh Village, Galis Subdistrict, Pamekasan Regency - Samsuki; Merie Satya Angraini; Anisah Choirunnisa; Erika Prilla Stevania; Intan Thalia (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: This community service activity aims to accelerate legal compliance among MSMEs in Ponteh Village, Pamekasan, by increasing understanding of SJPH and assisting with Halal Certificate applications through the Self-Declare Scheme. Method: This community service activity aims to accelerate legal compliance among MSMEs in Ponteh Village, Pamekasan, by increasing understanding of SJPH and assisting with Halal Certificate applications through the Self-Declare Scheme. Practical Applications: This accelerated mentoring model effectively addresses the digital and technical literacy barriers faced by micro MSMEs. The results can be replicated by other mentoring institutions to accelerate halal certification. Economically, this certification opens up wider market access and increases consumer confidence in local products. Conclusion: This program was very successful, with 100% of MSME partners successfully obtaining Halal Certificates. There was also a significant increase in partner knowledge (50%). The conclusion shows that the Self-Declare Scheme with intensive assistance is the most effective solution for micro MSMEs to achieve product legality.